Minat Masyarakat Nganjuk terhadap Jasa SPA Tradisional - Angelina Karisma Putri Kartika Sari, Sephia (Universitas Negeri Surabaya, 2021)
In recent years, the SPA industry has played an important role in Indonesia. Through traditional treatments in Indonesia using ingredients from nature by utilizing the wealth of abundant natural resources such as spices, you can choose to take care of yourself. By conducting field research, it was found that the Nganjuk people are quite selective in choosing good body care services because they know the importance of taking care of the body and also the importance of choosing the right type of body care for themselves, both in terms of needs, budget, and others. There are several factors that influence the Nganjuk community in choosing and using body care services, namely internal factors (motivation, knowledge, and perception) and factors from the surrounding environment (role and status, economic conditions, reference groups, and lifestyle). The interest of the Nganjuk community towards traditional SPA services is influenced by many factors and is very diverse. However, the majority of them routinely use traditional SPA services and some will use traditional SPA services as an option for future body treatments. For people who are not interested in traditional SPA services, they have also done their own body treatments at home. This shows that the Nganjuk people are literate about body and self care. Keywords: interest; nganjuk; society; spa; traditional